An asthmatic child with allergic bronchopulmonary aspergillosis (ABPA) - Özdemir, Öner (The Turkish Journal of Pediatrics, 2018)
Allergic bronchopulmonary aspergillosis (ABPA) results from a TH2 hypersensitivity lung disease in response to bronchial colonization of Aspergillus fumigatus in the respiratory tract. ABPA is a very rare disease in the pediatric population; the prevalence is anticipated to be about 1-2% in adult asthma patients and 2-15% in cystic fibrosis patients. In pediatric asthma patients, only rare case reports on ABPA have been published. We present a case of a 12-year-old boy admitted to our hospital with worsening (mild persistent) asthma symptoms such as a recurrent cough, episodic wheezing, and dyspnea for the last two years. He was diagnosed with pneumonia several times and suspected of having tuberculosis during this time. Chest X-ray showed bilaterally perihilar opacities and computed tomography findings revealed central bronchiectasis. With the clinical and laboratory findings, the patient fulfilled 7/8 major diagnostic criteria for ABPA. Treatment with oral corticosteroids and itraconazole was effective. To the best of our knowledge, this is the first reported case of pediatric ABPA with previously documented asthma from Turkey.
Keywords: allergic bronchopulmonary aspergillosis; aspergillus fumigatus; asthma; central bronchiectasis